"Paintings Fade Like Flowers": Pigment Analysis and Digital Reconstruction of a Faded Pink Lake Pigment in Vincent van Gogh's Undergrowth with Two Figures. Issue 5 (May 2017) - Fieberg, Jeffrey E.; Knutås, Per; Hostettler, Kurt; Smith, Gregory D.
Color fading in Vincent van Gogh's Undergrowth with Two Figures was studied chemically to facilitate the creation of a digital reconstruction of fugitive colors . The painting contains a field of white, green, orange, and yellow flowers under a canopy of poplar trees with two central figures—a man and a woman, arms entwined. From Van Gogh's letters, however, it is known that he painted the picture with some pink flowers, which appear to have altered, presumably to white. Raman spectroscopy was applied to microsamples of paint to identify the faded pigment as geranium lake, which in this painting consists of the dye, eosin (2′, 4′, 5′, 7′-tetrabromofluorescein). For the first time, lead(II) sulfate has been specifically identified as the likely inorganic substrate for a geranium lake used by Van Gogh in the last months of his life. Microfocus X-ray fluorescence (MXRF) spectroscopy was subsequently used in situ to analyze the white flowers to identify bromine as a proxy for eosin, thus indicating an original pink coloration. Of the 387 white flowers analyzed, 37.7% contained measurable bromine and were, therefore, originally pink. Several cross-sections from these formerly pink areas were assessed using a combination of visual inspection and microcolorimetry to create a colored mask in Adobe Photoshop to digitally reconstruct a suggestion of the original appearance of the painting with regard to the faded flowers. Additionally, microfadeometry was undertaken for the first time on a painting cross-section sample to understand the actual fading kinetics of the underlying bright pink geranium lake used by Van Gogh. A combination of Raman microspectroscopy, MXRF, and scanning electron microscopy energy dispersive spectroscopy (SEM-EDS) were utilized in situ and on paint microsamples to identify the complete palette used to create Undergrowth with Two Figures .